Repetitive transcranial magnetic stimulation for cerebellar ataxia: a systematic review and meta-analysis - Yin, Lianjun; Wang, Xiaoyu; Chen, Lianghua; Liu, Dandan; Li, Haihong; Liu, Zhaoxing; Huang, Yong; Chen, Junqi (Frontiers in Neurology, 2023)
Background Repetitive transcranial magnetic stimulation, a non-invasive brain stimulation technique, can manage cerebellar ataxia (CA) by suppressing cerebral cortical excitability. Hence, this study aimed to summarize the efficacy and safety of rTMS for CA patients by meta-analysis. Methods The PubMed, Embase, Web of Science, and Cochrane Library databases were searched for eligible studies published till 20 May 2023. Weighted mean difference (MD) and 95% confidence intervals (CIs) were used to assess the effect of rTMS treatment. Additionally, the quality of the included studies and the risk of bias were evaluated using the Physiotherapy Evidence Database (PEDro) scale. Results Overall, eight studies involving 278 CA patients were included in this meta-analysis. rTMS could significantly improve the Scale for the Assessment and Rating of Ataxia (SARA) (MD: −2.00; 95% CI: −3.97 to −0.02, p = 0.05), International Cooperative Ataxia Rating Scale (ICARS) (MD: −3.96; 95% CI: −5.51 to −2.40, p < 0.00001), Timed Up-and-Go test (TUG) (MD: −1.54; 95% CI: −2.24 to −0.84, p < 0.0001), 10-m walk test (10 MWT) (MD10−m steps: −2.44; 95% CI: −4.14 to −0.73, p = 0.005), and Berg Balance Scale (BBS) (MD: 2.59; 95% CI: 1.15–4.03, p = 0.0004) as compared to sham stimulation. Active rTMS was not significantly different from sham rTMS in changing the duration (MD10−m time: −1.29; 95% CI: −7.98 to 5.41, p = 0.71). No severe adverse events were observed in both sham stimulation and active rTMS groups. Conclusion This meta-analysis provides limited evidence that rTMS may be beneficial in treating CA patients. However, these findings should be treated with caution due to the limitations of the smaller sample size and the inconsistent approach and target of rTMS treatment. Therefore, more large-scale RCTs are required to further validate our analytical findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=295726, identifier: CRD42022295726.